The Influence of Good Corporate Governance, Corporate Social Responsibility, and Return on Assets on the Value of Islamic Banks - Gah, Tiffany Natalia Petronela; Wulandari, Agusta Amanda; Rupilu, Wilsna; Poeh, Melda Mariana (Celebes Scholar pg, 2025)
This paper examines the process by which Islamic commercial banks in Indonesia create firm value via the interaction of governance mechanisms, moral signaling, as well as, financial performance. Based on more or less numerous forms of multiple linear regression analyses in 12 Sharia compliance banking institutions between 2019 and 2022, the study will investigate the corresponding influence of Islamic Good Corporate Governance (IGCG), Islamic Corporate Social Responsibility (ICSR), and Return on Assets (ROA) on investor-scape perceived value reflecting through Earnings per Share (EPS). The results indicate a strong divergence between the formal systems of governance and market-imposed judgments. IGCG, although institutionally mandated, does not play any significant role in creating firm value, which implies that the current practice of governance is not publicly credible. Comparatively, ICSR has proven to be the most influential predictor representing that the stakeholders give more importance on ethical transparency rather than procedural compliance. ROA is an influential albeit minor element, which supports the idea that profitability is essential but not sufficient by itself to keep valuation trust. Such outcomes must herald a transformation in the vision of value in an Islamic finance context; in other words, how compliance is measured and appropriately valued financially is no longer an internalized affair because such reality is more seen in terms of filming the veracity of a financial institution publicly.